1999
DOI: 10.1038/21674
|View full text |Cite
|
Sign up to set email alerts
|

The TAK1–NLK–MAPK-related pathway antagonizes signalling between β-catenin and transcription factor TCF

Abstract: The Wnt signalling pathway regulates many developmental processes through a complex of beta-catenin and the T-cell factor/lymphoid enhancer factor (TCF/LEF) family of high-mobility-group transcription factors. Wnt stabilizes cytosolic beta-catenin, which then binds to TCF and activates gene transcription. This signalling cascade is conserved in vertebrates, Drosophila and Caenorhabditis elegans. In C. elegans, the proteins MOM-4 and LIT-1 regulate Wnt signalling to polarize responding cells during embryogenesi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
491
3
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 575 publications
(510 citation statements)
references
References 28 publications
15
491
3
1
Order By: Relevance
“…Although our results showed that TAK1 represses the hTERT promoter activity in an E-box-independent manner, we cannot exclude the possibility that TAK1 represses the hTERT promoter even in an E-box-dependent manner. In fact, a b-catenin/Tcf-4 complex augments c-Myc gene transcription by binding to the Tcf-4-binding sites in the c-Myc promoter (He et al, 1998); however, this binding is impaired by the MAPK-related NEMO-like kinase (NLK) pathway activated by TAK1 (Ishitani et al, 1999). Thus, in the future, we must investigate whether TAK1 represses c-Myc expression by activating the NLK pathway and consequently antagonizing the b-catenin/Tcf-4 complex and whether this c-Myc repression results in hTERT promoter repression in an E-box-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Although our results showed that TAK1 represses the hTERT promoter activity in an E-box-independent manner, we cannot exclude the possibility that TAK1 represses the hTERT promoter even in an E-box-dependent manner. In fact, a b-catenin/Tcf-4 complex augments c-Myc gene transcription by binding to the Tcf-4-binding sites in the c-Myc promoter (He et al, 1998); however, this binding is impaired by the MAPK-related NEMO-like kinase (NLK) pathway activated by TAK1 (Ishitani et al, 1999). Thus, in the future, we must investigate whether TAK1 represses c-Myc expression by activating the NLK pathway and consequently antagonizing the b-catenin/Tcf-4 complex and whether this c-Myc repression results in hTERT promoter repression in an E-box-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
“…Early studies showed that overexpressed Wnt5a can block the stabilization of β-catenin induced by Wnt-1 39 . Expression of Wnt5a can also activate a nemo-like kinase (NLK) that phosphorylates TCF transcription factors, thus inhibiting canonical Wnt signaling 40,41 . In fact, it appears that simply inhibiting canonical signaling can, in some conditions, lead to PCP effects.…”
Section: Crosstalk Between Various Wnt Pathwaysmentioning
confidence: 99%
“…Another β-catenin binding protein, ICAT, can block the binding of β-catenin to TCF [21] and also can lead to the dissociation of complexes between β-catenin, LEF, and CBP/p300 [22,23]. TCF can be phosphorylated by the mitogen-activated protein (MAP) kinase-related protein kinase NLK/Nemo [24]. The phosphorylation of TCF/LEF by activated Nemo is thought to diminish the DNA-binding affinity of the β-catenin/TCF/LEF complex, thereby affecting transcriptional regulation of Wnt target genes [24,25].…”
Section: Regulation Of Wnt Signalingmentioning
confidence: 99%
“…TCF can be phosphorylated by the mitogen-activated protein (MAP) kinase-related protein kinase NLK/Nemo [24]. The phosphorylation of TCF/LEF by activated Nemo is thought to diminish the DNA-binding affinity of the β-catenin/TCF/LEF complex, thereby affecting transcriptional regulation of Wnt target genes [24,25].…”
Section: Regulation Of Wnt Signalingmentioning
confidence: 99%